Impact of European integration on competitiveness of Czech Regions - Litva, Dušan (Business, Management and Economics Engineering, 2017)
Economic integration supports removal of all obstacles (in economy, trade, tax, administration or industrial area) and establishment of common rules for market competition. Basic benefit of economic integration is thus occurrence of real or potential competitiveness effects. European integration can influence competitiveness of firm, regions or countries. There are existing agglomeration forces causing space and economic concentration and disperse forces working just opposite way. Both effects are influenced by access to a single market and removal of trade barriers. As a consequence, agglomeration effects are expected to dominate. European Commission established RCI (Regional Competitiveness Index) to enable comparison of competitiveness of European regions. Aim of this study is exploration of changes in competitiveness of Czech regions after accession to the European Union as there are no studies analysing regional competitiveness in Czech Republic as a consequence of European integration process via index based approach. Analysis of z statistics of primarily data published by European Commission is used to evaluate theoretical concept of disperse and agglomeration forces. Based on RCI analysis are obvious growing discrepancies with dominant position of Prague and Central Bohemia in comparison with other Czech Regions. Significant differences can be seen in areas of innovations, business sophistication and education. On the opposite, positively can be evaluated lower variability of competitiveness between Czech regions in indicators of infrastructure, institutions and technological readiness. Those indicators could be influenced by European cohesive and regional politics. Decisions on governmental level should follow Europe 2020 strategy and transformation to knowledge based economy.